2014
DOI: 10.4209/aaqr.2013.04.0109
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and Concentration Distribution of Culturable Airborne Bacteria in Residential Environments in Beijing, China

Abstract: The present investigation was conducted to assess the culturable concentration and distribution characteristics of airborne bacteria in 31 homes with children aged from 1 to 10 years in Beijing, China. The results showed that the concentration of culturable airborne bacteria in these homes ranged from 47 colony forming units (CFU)/m 3 to 12341 CFU/m 3 , with a mean and a median of 1821 and 877 CFU/m 3 , respectively. A total of 632 bacterial isolates from the air in homes in different regions and different sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
5
26
0
Order By: Relevance
“…It was observed that all the sections sampled showed diverse bacterial loads similar to other studies conducted elsewhere 7,15 . In accordance with this study, frequent movements of students and workers from immediate-outdoor to the indoor environments decisively influenced the diversity and abundance of the isolated bacteria.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It was observed that all the sections sampled showed diverse bacterial loads similar to other studies conducted elsewhere 7,15 . In accordance with this study, frequent movements of students and workers from immediate-outdoor to the indoor environments decisively influenced the diversity and abundance of the isolated bacteria.…”
Section: Discussionsupporting
confidence: 72%
“…In a typical research environment of academic training and learning, a series of movements do occur from the outdoors through the immediateoutdoors to indoors 2,14 . This facilitates the movement of microorganisms, especially bacteria to different compartments of the building 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there are an increasing number of studies investigating bioaerosols from indoor and occupational environments including impacts from ambient ones (Hsu et al, 2012;Fang et al, 2014;Qian et al, 2014;Galès et al, 2015;Li et al, 2015;Sidra et al, 2015;Yamamoto et al, 2015;Goudarzi et al, 2016;Jahne et al, 2016;Li et al, 2016;Mirhoseini et al, 2016;Smets et al, 2016). Most recently, a research focus has been developed, particularly for the bioaerosol emission from human occupancy in an indoor environment.…”
Section: Introductionmentioning
confidence: 99%
“…16s rDNA sequencing analysis was done at Triyat Scientific Co., Nagpur, India. PCR amplification of 16s region was carried out following the protocol described previously (Fang et al, 2014) using 27F (AGA GTT TGA TCC TGG CTC AG) and 1522R (AAG GAG GTG ATC CAG CCG CA) universal primers set. The amplified products were purified and then subjected to automated DNA sequencing using Applied Biosystems genetic analyzer following the manufacturer's instruction.…”
Section: Microbial Identification Bacterial Identificationmentioning
confidence: 99%